KECEMASAN IBU HAMIL PADA MASA PANDEMI COVID-19 DI BIDAN SURATMI KOTA BATAM - Rahmawati; Silvia Mona; T. Marzila Fahnawal (Universitas Batam, 2022)
COVID-19 has an impact on people's welfare which can be a psychological problem for pregnant women, one of which is anxiety. The purpose of this study was to describe the anxiety of pregnant women and postpartum mothers during the COVID-19 pandemic. The research design is descriptive research. The research sample was 30 pregnant women in PMB Suratmi Batam City with cluster sampling technique. The instrument used was the perinatal anxiety screening scale (PASS). As a result, pregnant women in PMB Suratmi, Batam City, during the COVID-19 pandemic, the majority experienced mild-moderate anxiety, amounting to 22 respondents with a percentage of 73.3%. Suggestions in this study should be to increase the number of respondents by expanding the population scale. As well as increasing homecare services for pregnant women.